Effect of hydrogen peroxide 25% on microhardness of dental enamel - Sánchez Gamarra, Vania (2013)
The aim was determinate the effect of two bleaching agents based on hydrogen peroxide 25% on dental enamel microhardness. An experimental study was made to evaluate the effect of hydrogen peroxide 25% on the enamel surface microhardness, it was used 30 extracted premolars with orthodontic purposes, which were sectioned and placed in a mold of 1 cm circumferential in diameter and 1cm thick,filling with acrylic self-curing color red (15) and blue (15) storing in sterile flasks containing physiological serum. An initial measurement was using the BUEHLER MICROMET 2101 microhardness in the Sputtering Laboratory, Faculty of Science, National University of Engineering, applied a load of 100g for 30 seconds, then proceeded to measure the indentation to find the measure of microhardness in kg/mm2. Then group 1 was done bleaching with Peroxgel MCC and group 2 with Zoom2, the next day again measured enamel microhardness. The results of the enamel surface microhardness of the whitening agent: Peroxgel MCC and Zoom2, showed a statistically significant decrease (234.83 Kgf/mm2) and (196.11 Kgf/mm2) respectively, found no significant difference (p = 0.136) when comparing the decline between bleaching agents used in this study. It is concluded that the use of bleaching agents based on hydrogen peroxide 25% decreased significantly the microhardness of the enamel surface.